Agarwood (Aquilaria malaccensis) diversity conservation by in vitro culture with IAA and yeast extract (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Samanhudi, Sakya AT, Setyawati A, Muawanah M. 2022. Agarwood (Aquilaria malaccensis) diversity conservation by in vitro culture with IAA and yeast extract. Biodiversitas 23: 2457-2463. Agarwood (Aquilaria malaccensis) is a scare plant with high economic value and many benefits. Tissue culture is an effective way of producing plants in large quantities, in a short time with uniform results. This study aims to get the proper concentration of IAA and yeast extract for agarwood growth in vitro. The research was conducted in December 2019-June 2020 at the Laboratory of Plant Physiology and Plant Biotechnology, Faculty of Agriculture, Universitas Sebelas Maret, Surakarta. The design used is Randomized Complete Block Design (RCBD) in 2 factors: first factor was IAA concentration with 4 level: 0; 0,5; 1; 1.5 mgL-1 and second factor was yeast extract concentration with 4 levels: 0; 200; 400; 800 mgL-1. Obtained 16 combinations of treatments repeated 3 times so that there are 48 units of experiments. Observed variables: the time of appearance of shoots, the number of shoots, the height of shoots, the number of leaves, and the number of roots. Root count data is described and data other than root count is analyzed ANOVA, if real influence is further tested DMRT 5%. The IAA affects the height of shoots and the number of agarwood leaves in vitro rooted plantlets has 5 plantlets.
Keywords: gaharu, Aquilaria malaccensis, in vitro, IAA, yeast extract